2022
DOI: 10.1039/d1tc05171g
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance humidity sensor based on alkalized MXenes and poly(dopamine) for touchless sensing and respiration monitoring

Abstract: The typical mode of interaction between humans and machines in current intelligent equipment and personalized health care systems is mainly contact-type. However, there are severe problems associated with direct contact,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Ullah et al reported a highly sensitive, flexible, and eco-friendly biodegradable nonwoven paper-based humidity sensor on polyethylene terephthalate (PET) substrate with copper tape as electrodes and demonstrated its applications in health and medicine . In recent work, Li et al proposed a flexible humidity sensor based on alkalized MXenes and polydopamine for human–machine interaction in a noncontact manner . Such studies suggest the emerging application of humidity sensors in determining human health severities related to respiration and skin moisture.…”
Section: Resultsmentioning
confidence: 99%
“…Ullah et al reported a highly sensitive, flexible, and eco-friendly biodegradable nonwoven paper-based humidity sensor on polyethylene terephthalate (PET) substrate with copper tape as electrodes and demonstrated its applications in health and medicine . In recent work, Li et al proposed a flexible humidity sensor based on alkalized MXenes and polydopamine for human–machine interaction in a noncontact manner . Such studies suggest the emerging application of humidity sensors in determining human health severities related to respiration and skin moisture.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, the first Ti 3 C 2 T x MXene humidity sensor was demonstrated, 24 and various strategies have been explored to boost their sensing performance. Ion intercalation (K + , Mg 2+ , or Na + ), 25 and hybridization with Ag, 26 TiO 2 , 27 K 2 Ti 4 O 9 , 28 and water-sensitive polyelectrolytes 29–31 have been utilized to promote the responsiveness (response and recovery time) of the MXene humidity sensors. Moreover, Ti 3 C 2 T x MXene has proved to be sensitive to low concentrations of gas vapors, 32,33 and thus the pristine Ti 3 C 2 T x may display a poor selectivity for water.…”
Section: Introductionmentioning
confidence: 99%
“…Ion intercalation [ 45 ] (e.g., K + , Mg 2+ , or Na + ) in the pristine MXenes structures has been used to promote the diffusion of water in the material, improving its sensitivity toward moisture. Hybridization with Ag nanowires, [ 46 ] titanium dioxide (TiO 2 ), [ 47 ] K 2 Ti 4 O 9 nanowires, [ 48 ] and water‐sensitive polyelectrolytes such as poly(vinyl alcohol) (PVA), [ 49 ] poly(dopamine) (PDA), [ 50 ] or poly(diallyldimethylammonium chloride) (PDAC) [ 51 ] has been employed to increase the responsiveness (i.e., response and recovery time) of pristine MXenes. The intercalation of TiOF 2 nanospheres [ 52 ] in the pristine MXenes, or their hybridization with sodium ascorbate [ 53 ] or sodium alginate [ 54 ] showed improved long‐term stability.…”
Section: Introductionmentioning
confidence: 99%